Men at lunch / [videorecording (DVD)] (First Run Features, 2013)
In New York City, 1932, a photograph, "Lunch atop a Skyscraper," is taken during the construction of 30 Rockefeller Plaza. In it, eleven workmen are taking their lunch break while casually perched along a steel girder. For 80 years, the identity of the eleven men and the photographer that immortalized them remained a mystery: their stories, lost in time, subsumed by the fame of the image itself. Then, at the start of the 21st century, the photograph finally began to give up some of its secrets.